2018
DOI: 10.1038/s41598-018-30859-y
|View full text |Cite
|
Sign up to set email alerts
|

ZNF542P is a pseudogene associated with LDL response to simvastatin treatment

Abstract: Statins are the most commonly prescribed cardiovascular disease drug, but their inter-individual efficacy varies considerably. Genetic factors uncovered to date have only explained a small proportion of variation in low-density lipoprotein cholesterol (LDLC) lowering. To identify novel markers and determinants of statin response, we used whole transcriptome sequence data collected from simvastatin and control incubated lymphoblastoid cell lines (LCLs) established from participants of the Cholesterol and Pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Simvastatin treatment reduces the risk of cardiovascular events and cardiovascular disease-related deaths, predominantly by decreasing intracellular and circulating cholesterol levels [7,8,9,10]; however, the role of simvastatin in ECs remains unclear. In this study, we found that low simvastatin doses increased the viability of HUVECs while high doses reduced their viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin treatment reduces the risk of cardiovascular events and cardiovascular disease-related deaths, predominantly by decreasing intracellular and circulating cholesterol levels [7,8,9,10]; however, the role of simvastatin in ECs remains unclear. In this study, we found that low simvastatin doses increased the viability of HUVECs while high doses reduced their viability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, simvastatin suppresses atherosclerotic lesion formation in ApoE KO mice by down-regulating CD36 and calpain-1, thus reducing inflammation [7]. In clinical trials, simvastatin significantly reduced the circulating levels of total cholesterol, LDL-C, VLDL-C, and LDL-C, which are considered risk factors for AS [8,9,10]. Although simvastatin is recognized for its anti-arterial AS effects, the specific mechanism underlying its effects on oxidative stress-induced EC dysfunction remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They further showed that knock-down of the ZNF542P gene in a human hepatoma cell line increases the intracellular levels of cholesterol ester after the cells were exposed to simvastatin. These findings indicate that ZNF542P may have a role in low-density lipoprotein cholesterol (LDL-C) response to simvastatin (Kim et al, 2018 ). However, since these genes were identified from cell lines, not directly from tissues of patients treated with simvastatin, it is likely that they might not be the most responsive genes in vivo .…”
Section: Pseudogenes and Cvdsmentioning
confidence: 99%
“…Using the same approach, but this time with RNA-seq data from both simvastatin and sham-treated CAP LCLs, we sought to identify genes whose statin-induced expression changes were most different between individuals in the tails of the LDL-C statin response distribution. We created a classification model of 82 signature gene expression changes that distinguished high versus low LDL-C statin response [49]. One of the most differentially changing signature genes was ZNF542P, a pseudogene whose expression change was found to be most strongly correlated with statin-induced change in LCL cellular cholesterol ester, an in vitro marker of statin response [49].…”
Section: Transcriptomic Correlation -Dna Variation: Cellular Phenotype (Eqtls and Deqtls)mentioning
confidence: 99%
“…We created a classification model of 82 signature gene expression changes that distinguished high versus low LDL-C statin response [49]. One of the most differentially changing signature genes was ZNF542P, a pseudogene whose expression change was found to be most strongly correlated with statin-induced change in LCL cellular cholesterol ester, an in vitro marker of statin response [49]. These results, together with those for RP1-13D10.2 described above, point to the value of RNA-seq of statin and sham-exposed LCLs for identifying nonprotein coding transcripts with regulatory functions that may contribute to variation in response to statin.…”
Section: Transcriptomic Correlation -Dna Variation: Cellular Phenotype (Eqtls and Deqtls)mentioning
confidence: 99%